Functional expression of mouse mdr1 in Escherichia coli. - Bibi, E (1993)
We describe functional expression of the mouse multidrug-resistance protein (P-glycoprotein; P-gp) in an Escherichia coli mutant defective in the outer membrane protease ompT. Heterologously expressed mdr1 appears as an unglycosylated species with an apparent molecular mass of 140 kDa in the membrane of the mutant. Unglycosylated mdr1 retains the ability to bind the photoactivatable drug analog [125I]iodoarylazidoprazosin and confers resistance to tetraphenylphosphonium (TPP+) and tetraphenylarsonium (TPA+), known mdr1 substrates. In vivo resistance is linked to reduced cellular accumulation and energy-dependent efflux of the lipophilic cations. Surprisingly, discrete mutations in the predicted nucleotide binding folds of mdr1 that abolish drug resistance in mammalian cells have no apparent effect on TPA+ efflux via mdr1 in E. coli.